2011
DOI: 10.1586/erm.11.43
|View full text |Cite
|
Sign up to set email alerts
|

Copy-number changes in prenatal diagnosis

Abstract: Until recently, the prenatal detection of genetic disease was available to only a subset of the pregnant population deemed to be at an increased risk for chromosomal abnormalities or, more rarely, other genetic disorders, based on family history, multiple-marker screening or ultrasound findings. Guided by recent data that indicate that screening for Down syndrome has improved and that risks of invasive procedures are smaller than previously ascertained, the American College of Obstetricians and Gynecologists h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 101 publications
0
36
0
2
Order By: Relevance
“…However, the challenge of counseling couples about unpredictable outcomes is not new. 26 We observed a recurrent variant of unknown significance in a telomeric region of chromosome 19p13.3 (ranging in size from 632 to 930 kb) in eight stillbirths. This region is known to contain multiple benign variants as well as five loci in the OMIM database that have been associated with disease but not with stillbirth or developmental disorders.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…However, the challenge of counseling couples about unpredictable outcomes is not new. 26 We observed a recurrent variant of unknown significance in a telomeric region of chromosome 19p13.3 (ranging in size from 632 to 930 kb) in eight stillbirths. This region is known to contain multiple benign variants as well as five loci in the OMIM database that have been associated with disease but not with stillbirth or developmental disorders.…”
Section: Discussionmentioning
confidence: 86%
“…However, inherited pathogenic variants should not be discounted as a cause of stillbirth because of their variable expressivity and incomplete penetrance. 8,26 Our ability to assess confined placental mosaicism, in which the fetus is genetically normal but the placenta is genetically abnormal, was limited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, one might argue that the use of genome-wide array in prenatal diagnostics should not be restricted to pregnancies with ultrasound abnormalities [Strassberg et al, 2011]. On the other hand, the interpretation of array results is challenging, especially in the absence of ultrasound abnormalities, as pathogenic CNVs that do not result in a phenotype detectable by ultrasound may sometimes be hard to distinguish from benign CNVs.…”
Section: Introductionmentioning
confidence: 99%
“…However, the fact that only a minority of the submicroscopic abnormalities that are detected in postnatal patients with developmental delay/intellectual disability are accompanied by congenital abnormalities detectable by prenatal ultrasound, suggests the use of CMA in prenatal diagnostics not only for pregnancies with ultrasound abnormalities. 32 In the absence of specific guidelines and large-scale studies for different categories of indications, it has been suggested that CMA should be offered as an adjunction tool to selected groups of high-risk pregnancies (eg abnormal ultrasound findings and a normal conventional karyotype), using the technique as a second-line test only, after a standard karyotype. 25 Recently, the Canadian College of Medical Geneticists (CCMG) has discouraged the use of CMA in pregnancies at low risk for a structural chromosomal abnormality (eg advanced maternal age, positive maternal serum screen, previous pregnancy with a chromosomal abnormality or the presence of 'soft markers' on fetal ultrasound), motivating their position with the fact that CMA performed for the above categories of pregnancies would likely be associated with a low positive predictive value, since the vast majority of fetuses in these situations would be clinically unaffected.…”
Section: Introductionmentioning
confidence: 99%